Carbon-coated aluminum foil conductive paint

CN120795708BActive Publication Date: 2026-10-09YUQIANG NEW MATERIALS (HUBEI) CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511022661.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-24
Publication Date
2026-10-09
Estimated Expiration
2045-07-24

AI Technical Summary

Technical Problem

[0003]本发明的目的在于提供一种涂碳铝箔导电涂料,解决现阶段涂碳铝箔在加工过程中表面涂层易出现断裂破损的问题

Benefits of technology

[0014] During the coating drying process, the thiol groups in the modified polyacrylic acid molecules can form coordination bonds with silver powder and silver ions, thereby strengthening the contact between the silver powder and the modified polyacrylic acid and facilitating the formation of conductive pathways. In the preparation process of modified polyacrylic acid, modified monomers are added, which enables the modified polyacrylic acid molecules to form a dynamic cross-linked network, thereby increasing the mechanical properties of the coating and reducing the coating thickness. Even with a low thickness, the coating function can still be guaranteed, thereby improving the battery energy density. Furthermore, the surface coating is less prone to breakage during the welding process of carbon-coated aluminum foil. The organosilicon segments and fluorine elements contained in the modified polyacrylic acid molecules can inhibit electrolyte penetration, ensuring the adhesion of the coating. The coating will not peel off after multiple battery cycles, increasing the battery's lifespan.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a carbon-coated aluminum foil conductive coating and relates to the field of conductive coatings. The carbon-coated aluminum foil conductive coating comprises the following raw materials in parts by weight: 3-10 parts of conductive carbon black, 90-97 parts of few-layer graphene, 100-150 parts of modified polyacrylic acid, 3-5 parts of silver powder, 15-30 parts of polyvinylpyrrolidone and 500-1500 parts of solvent. In the preparation process of the modified polyacrylic acid, a modified monomer is added, so that the modified polyacrylic acid molecules form a dynamic crosslinking network, thereby increasing the mechanical properties of the coating and reducing the thickness of the coating. In the case of low thickness, the coating film function can still be guaranteed, thereby improving the energy density of the battery. In the welding process of the carbon-coated aluminum foil, the surface coating is not prone to breaking. The organic silicon chain segments and fluorine elements contained in the modified polyacrylic acid molecules can inhibit the penetration of the electrolyte, thereby guaranteeing the adhesion of the coating. After the battery is cycled for multiple times, the coating does not fall off, thereby increasing the service life of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of conductive coating preparation technology, specifically to a carbon-coated aluminum foil conductive coating. Background Technology

[0002] Lithium-ion batteries are widely used in various fields, such as digital products, power, and energy storage, due to their advantages such as high energy density, high voltage, wide operating temperature range, no memory effect, good cycle performance, and long service life. However, lithium batteries also have problems such as poor conductivity, low rate performance, and poor heat dissipation, which affect their further promotion and application. Lithium-ion batteries generally use aluminum foil or carbon-coated aluminum foil as the carrier of positive electrode material. Coating the surface of aluminum foil with a conductive carbon layer can suppress battery polarization, reduce thermal effects, and improve the rate performance of the battery. However, at present, the coating thickness on the surface of carbon-coated aluminum foil is too thick, which will affect the volumetric energy density of the battery. In order to increase the volumetric energy density of the battery, the thickness of the conductive coating on the carbon-coated aluminum foil is reduced. The reduced coating will be damaged during processing or welding, resulting in surface coating cracking, which in turn affects the normal use of the battery. Summary of the Invention

[0003] The purpose of this invention is to provide a conductive coating for carbon-coated aluminum foil, which solves the problem that the surface coating of carbon-coated aluminum foil is prone to breakage and damage during the current processing.

[0004] The objective of this invention can be achieved through the following technical solutions: A conductive coating for carbon-coated aluminum foil is prepared by the following steps: Step A1: Mix acrylic acid, diethanolamine, p-toluenesulfonic acid, hydroquinone, and DMF evenly, purge with nitrogen, and react for 2-3 hours at a speed of 120-150 r / min and a temperature of 80-85℃ to obtain intermediate one. Mix intermediate one, mercaptoacetic acid, p-toluenesulfonic acid, and DMF evenly, and react for 6-8 hours at a speed of 200-300 r / min and a temperature of 110-115℃ to obtain the modifier. Step A2: Mix acrylic acid, acrylamide, acrylonitrile, and DMF evenly. Stir and add azobisisobutyronitrile at a speed of 150-200 r / min and a temperature of 70-80℃. After reacting for 15-20 min, add the modified monomer and continue reacting for 2-4 h. Adjust the pH value to 6-6.5 to obtain pretreated polyacrylic acid. Mix the pretreated acrylic acid, modifier, chloroplatinic acid, and DMF evenly. React at a speed of 200-300 r / min and a temperature of 75-85℃ for 6-8 h to obtain modified polyacrylic acid. Step A3: Weigh the following raw materials in parts by weight: 3-10 parts conductive carbon black, 90-97 parts few-layer graphene, 100-150 parts modified polyacrylic acid, 3-5 parts silver powder, 15-30 parts polyvinylpyrrolidone, and 500-1500 parts solvent. Mix the raw materials evenly to obtain a carbon-coated aluminum foil conductive coating.

[0005] Furthermore, in the preparation of intermediate one described in step A1, the molar ratio of acrylic acid and diethanolamine is 1:1, the amount of p-toluenesulfonic acid is 1% of the mass of ethylene glycolamine, and the amount of hydroquinone is 1‰ of the mass of ethylene glycolamine. In the preparation of the modifier, the molar ratio of intermediate one and mercaptoacetic acid is 1:2, and the amount of p-toluenesulfonic acid is 1.5% of the mass of intermediate one.

[0006] Further, in step A2, the weight ratio of acrylic acid, acrylamide, acrylonitrile, and the modifying monomer is 60-70:20-30:10-15:2-4, the amount of azobisisobutyronitrile is 3‰ of the sum of the mass of acrylic acid, acrylamide, and acrylonitrile, the molar ratio of the Si-H bond on the pretreated acrylic acid to the modifier is 1:1, and the amount of chloroplatinic acid is 1‰ of the mass of the modifier.

[0007] Furthermore, the few-layer graphene mentioned in step A3 has 2-10 layers, a particle size of less than 10 μm, a silver powder particle size of 3 μm, a polyvinylpyrrolidone of type K30, and a solvent of deionized water and an alcohol in any proportion, wherein the alcohol is one or more of ethanol, n-propanol, isopropanol and n-butanol in any proportion.

[0008] Furthermore, the modified monomer is prepared by the following steps: Step B1: Mix p-phenylenediamine, allyl alcohol glycidyl ether, and DMF, and react for 3-5 hours at a rotation speed of 120-150 r / min, a temperature of 60-70℃, and a pH of 11-12 to obtain intermediate two. Mix intermediate two, p-nitrophenylboronic acid, and DMF, and under nitrogen protection, react for 3-5 hours at a rotation speed of 150-200 r / min, a temperature of 110-115℃, and a pH of 7.5-8 to obtain intermediate three. Step B2: Mix intermediate tri, trichlorosilane, chloroplatinic acid and DMF evenly, purge with nitrogen, and react for 6-8 hours at a speed of 200-300 r / min and a temperature of 75-85℃ to obtain intermediate tetra. Mix lithium dimethylhydrosilyl alcohol and DMF, stir and add trifluoropropylmethylcyclotrisiloxane at a speed of 150-200 r / min and a temperature of 0℃, raise the temperature to 25-30℃ and react for 20-24 hours. Then add the modifier and continue the reaction for 1-1.5 hours to obtain modified polysiloxane. Step B3: Mix the modified polysiloxane, zinc powder, deionized water and DMF evenly. Stir and add concentrated hydrochloric acid at a speed of 60-80 r / min and a temperature of 90-95℃ for 3-4 hours to obtain the aminated polysiloxane. Mix the aminated polysiloxane, p-toluenesulfonic acid and 4A molecular sieve and DMF evenly. Stir and add cinnamaldehyde at a speed of 300-500 r / min and a temperature of 50-60℃ for 5-7 hours to obtain the modified monomer.

[0009] Furthermore, the molar ratio of p-phenylenediamine and allyl alcohol glycidyl ether in step B1 is 1:4, and the molar ratio of intermediate di and p-nitrophenylboronic acid is 1:2.

[0010] Furthermore, in step B2, the molar ratio of intermediate tri and trichlorosilane is 1:4, the amount of chloroplatinic acid is 1‰ of the mass of trichlorosilane, and the molar ratio of lithium dimethylhydrosilyl alcohol, trifluoropropylmethylcyclotrisiloxane and Si-Cl on intermediate tetra is 1:5:1.

[0011] Furthermore, in step B3, the ratio of modified polysiloxane, zinc powder, deionized water, DMF and concentrated hydrochloric acid is 152g:15g:50mL:200mL:50mL, the mass fraction of concentrated hydrochloric acid is 36%, the molar ratio of amino group and cinnamaldehyde on the aminated polysiloxane is 1:1, and the amount of p-toluenesulfonic acid is 1%.

[0012] The beneficial effects of the present invention are as follows: The conductive coating for carbon-coated aluminum foil prepared by the present invention includes the following raw materials: conductive carbon black, few-layer graphene, modified polyacrylic acid, silver powder, polyvinylpyrrolidone and solvent. The modified polyacrylic acid is prepared by using acrylic acid and diethanolamine as raw materials, so that the carboxyl groups on the acrylic acid and the secondary amine on the diethanolamine undergo dehydration reaction to obtain intermediate one. Intermediate one is reacted with mercaptoacetic acid, so that the hydroxyl groups on the intermediate one and the carboxyl groups on the mercaptoacetic acid react to obtain a modifier. Acrylic acid, acrylamide, acrylonitrile and the modified monomer are polymerized to obtain pretreated polyacrylic acid. The pretreated polyacrylic acid and the modifier are reacted under the action of chloroplatinic acid, so that the Si-H bonds on the pretreated polyacrylic acid and the double bonds on the modifier react to obtain modified polyacrylic acid.

[0013] The modified monomers are p-phenylenediamine and allyl alcohol glycidyl ether. The amino group on p-phenylenediamine reacts with the epoxy group on allyl alcohol glycidyl ether to form a hydroxyl group, yielding intermediate two. Intermediate two is then reacted with p-nitrophenylboronic acid, causing the diol on the same side of intermediate two to react with the boric acid on p-nitrophenylboronic acid, forming a borate ester structure, yielding intermediate three. Intermediate three is then reacted with trichlorosilane, causing the double bond on intermediate three to react with the Si-H bond on trichlorosilane, yielding intermediate four. Using lithium dimethylhydrosilyl alcohol as an initiator and trifluoropropylmethylcyclotrisiloxane as a polymerization monomer, a modifier is added to react the Si-Cl on the modifier with the lithium silyl alcohol to obtain a modified polysiloxane. The modified polysiloxane is then reduced with zinc powder to convert the nitro group on the modified polysiloxane into an amino group, thus obtaining an aminated polysiloxane. The aminated polysiloxane is then reacted with cinnamaldehyde to react the amino group on the aminated polysiloxane with the aldehyde group on the cinnamaldehyde to form an imine structure, thus obtaining the modified monomer.

[0014] During the coating drying process, the thiol groups in the modified polyacrylic acid molecules can form coordination bonds with silver powder and silver ions, thereby strengthening the contact between the silver powder and the modified polyacrylic acid and facilitating the formation of conductive pathways. In the preparation process of modified polyacrylic acid, modified monomers are added, which enables the modified polyacrylic acid molecules to form a dynamic cross-linked network, thereby increasing the mechanical properties of the coating and reducing the coating thickness. Even with a low thickness, the coating function can still be guaranteed, thereby improving the battery energy density. Furthermore, the surface coating is less prone to breakage during the welding process of carbon-coated aluminum foil. The organosilicon segments and fluorine elements contained in the modified polyacrylic acid molecules can inhibit electrolyte penetration, ensuring the adhesion of the coating. The coating will not peel off after multiple battery cycles, increasing the battery's lifespan. Detailed Implementation

[0015] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0016] Example 1: A conductive coating for carbon-coated aluminum foil is prepared by the following steps: Step A1: Acrylic acid, diethanolamine, p-toluenesulfonic acid, hydroquinone and DMF are mixed evenly, and nitrogen gas is introduced for protection. The mixture is reacted for 2 hours at a speed of 120 r / min and a temperature of 80℃ to obtain intermediate one. Intermediate one, mercaptoacetic acid, p-toluenesulfonic acid and DMF are mixed evenly and reacted for 6 hours at a speed of 200 r / min and a temperature of 110℃ to obtain the modifier. Step A2: Mix acrylic acid, acrylamide, acrylonitrile, and DMF evenly. Stir and add azobisisobutyronitrile at 150 r / min and 70°C. After reacting for 15 min, add the modified monomer and continue reacting for 2 h. Adjust the pH to 6 to obtain pretreated polyacrylic acid. Mix the pretreated acrylic acid, modifier, chloroplatinic acid, and DMF evenly. React at 200 r / min and 75°C for 6 h to obtain modified polyacrylic acid. Step A3: Weigh the following raw materials in parts by weight: 3 parts conductive carbon black, 90 parts few-layer graphene, 100 parts modified polyacrylic acid, 3 parts silver powder, 15 parts polyvinylpyrrolidone, and 500 parts solvent. Mix the raw materials evenly to obtain a carbon-coated aluminum foil conductive coating.

[0017] In the preparation of intermediate one described in step A1, the molar ratio of acrylic acid and diethanolamine is 1:1, the amount of p-toluenesulfonic acid is 1% of the mass of ethylene glycolamine, and the amount of hydroquinone is 1‰ of the mass of ethylene glycolamine. In the preparation of the modifier, the molar ratio of intermediate one and mercaptoacetic acid is 1:2, and the amount of p-toluenesulfonic acid is 1.5% of the mass of intermediate one.

[0018] The weight ratio of acrylic acid, acrylamide, acrylonitrile and the modifying monomer in step A2 is 60:20:10:2. The amount of azobisisobutyronitrile is 3‰ of the sum of the mass of acrylic acid, acrylamide and acrylonitrile. The molar ratio of Si-H bonds on the pretreated acrylic acid to the modifier is 1:1. The amount of chloroplatinic acid is 1‰ of the mass of the modifier.

[0019] The few-layer graphene mentioned in step A3 has 2 layers and a particle size of 8 μm. The silver powder has a particle size of 3 μm. The polyvinylpyrrolidone is of type K30. The solvent is a mixture of deionized water, ethanol and n-propanol in a mass ratio of 10:8:3.

[0020] The modified monomer is prepared by the following steps: Step B1: p-phenylenediamine, allyl alcohol glycidyl ether and DMF are mixed and reacted for 3 hours at a speed of 120 r / min, a temperature of 60℃ and a pH of 11 to obtain intermediate two. Intermediate two, p-nitrophenylboronic acid and DMF are mixed and reacted under nitrogen protection at a speed of 150 r / min, a temperature of 110℃ and a pH of 7.5 for 3 hours to obtain intermediate three. Step B2: Intermediate tri, trichlorosilane, chloroplatinic acid and DMF are mixed evenly, and nitrogen gas is introduced for protection. The mixture is reacted for 6 hours at a speed of 200 r / min and a temperature of 75°C to obtain intermediate tetra. Lithium dimethylhydrosilyl alcohol and DMF are mixed and stirred at a speed of 150 r / min and a temperature of 0°C. Trifluoropropylmethylcyclotrisiloxane is added, the temperature is raised to 25°C, and the mixture is reacted for 20 hours. Then, a modifier is added, and the reaction is continued for 1 hour to obtain modified polysiloxane. Step B3: Mix the modified polysiloxane, zinc powder, deionized water and DMF evenly, stir and add concentrated hydrochloric acid at 60 r / min and 90 ℃, and react for 3 h to obtain the aminated polysiloxane. Mix the aminated polysiloxane, p-toluenesulfonic acid and 4A molecular sieve and DMF evenly, stir and add cinnamaldehyde at 300 r / min and 50 ℃, and react for 5 h to obtain the modified monomer.

[0021] The molar ratio of p-phenylenediamine and allyl alcohol glycidyl ether in step B1 is 1:4, and the molar ratio of intermediate di and p-nitrophenylboronic acid is 1:2.

[0022] The molar ratio of intermediate tri and trichlorosilane in step B2 is 1:4, the amount of chloroplatinic acid is 1‰ of the mass of trichlorosilane, and the molar ratio of lithium dimethylhydrosilyl alcohol, trifluoropropylmethylcyclopH trisiloxane and Si-Cl on intermediate tetra is 1:5:1.

[0023] The ratio of modified polysiloxane, zinc powder, deionized water, DMF and concentrated hydrochloric acid in step B3 is 152g:15g:50mL:200mL:50mL, the mass fraction of concentrated hydrochloric acid is 36%, the molar ratio of amino group and cinnamaldehyde on the aminated polysiloxane is 1:1, and the amount of p-toluenesulfonic acid is 1%.

[0024] Example 2, a conductive coating for carbon-coated aluminum foil, is prepared by the following steps: Step A1: Acrylic acid, diethanolamine, p-toluenesulfonic acid, hydroquinone and DMF are mixed evenly, and nitrogen gas is introduced for protection. The mixture is reacted for 2 hours at a speed of 120 r / min and a temperature of 85℃ to obtain intermediate one. Intermediate one, mercaptoacetic acid, p-toluenesulfonic acid and DMF are mixed evenly and reacted for 7 hours at a speed of 300 r / min and a temperature of 113℃ to obtain the modifier. Step A2: Mix acrylic acid, acrylamide, acrylonitrile, and DMF evenly. Stir and add azobisisobutyronitrile at 150 r / min and 75°C. After reacting for 18 min, add the modified monomer and continue reacting for 3 h. Adjust the pH to 6.5 to obtain pretreated polyacrylic acid. Mix the pretreated acrylic acid, modifier, chloroplatinic acid, and DMF evenly. React at 200 r / min and 80°C for 7 h to obtain modified polyacrylic acid. Step A3: Weigh the following raw materials in parts by weight: 6 parts conductive carbon black, 93 parts few-layer graphene, 125 parts modified polyacrylic acid, 4 parts silver powder, 23 parts polyvinylpyrrolidone, and 1000 parts solvent. Mix the raw materials evenly to obtain a carbon-coated aluminum foil conductive coating.

[0025] In the preparation of intermediate one described in step A1, the molar ratio of acrylic acid and diethanolamine is 1:1, the amount of p-toluenesulfonic acid is 1% of the mass of ethylene glycolamine, and the amount of hydroquinone is 1‰ of the mass of ethylene glycolamine. In the preparation of the modifier, the molar ratio of intermediate one and mercaptoacetic acid is 1:2, and the amount of p-toluenesulfonic acid is 1.5% of the mass of intermediate one.

[0026] The weight ratio of acrylic acid, acrylamide, acrylonitrile and the modifying monomer in step A2 is 65:25:12:3. The amount of azobisisobutyronitrile is 3‰ of the sum of the mass of acrylic acid, acrylamide and acrylonitrile. The molar ratio of Si-H bonds on the pretreated acrylic acid to the modifier is 1:1. The amount of chloroplatinic acid is 1‰ of the mass of the modifier.

[0027] The few-layer graphene mentioned in step A3 has 5 layers and a particle size of 8 μm. The silver powder has a particle size of 3 μm. The polyvinylpyrrolidone is of type K30. The solvent is a mixture of deionized water, ethanol, n-propanol and isopropanol in a mass ratio of 15:3:3:1.

[0028] The modified monomer is prepared by the following steps: Step B1: p-phenylenediamine, allyl alcohol glycidyl ether and DMF are mixed and reacted for 4 hours at a speed of 120 r / min, a temperature of 65℃ and a pH of 12 to obtain intermediate two. Intermediate two, p-nitrophenylboronic acid and DMF are mixed and reacted under nitrogen protection at a speed of 150 r / min, a temperature of 113℃ and a pH of 8 for 4 hours to obtain intermediate three. Step B2: Intermediate tri, trichlorosilane, chloroplatinic acid and DMF are mixed evenly, and nitrogen gas is introduced for protection. The mixture is reacted for 7 hours at a speed of 200 r / min and a temperature of 80 °C to obtain intermediate tetra. Lithium dimethylhydrosilyl alcohol and DMF are mixed and stirred at a speed of 150 r / min and a temperature of 0 °C. Trifluoropropylmethylcyclotrisiloxane is added, the temperature is raised to 28 °C, and the mixture is reacted for 22 hours. Then, a modifier is added, and the reaction is continued for 1.3 hours to obtain modified polysiloxane. Step B3: Mix the modified polysiloxane, zinc powder, deionized water and DMF evenly, stir and add concentrated hydrochloric acid at 60 r / min and 93℃, and react for 3.5 h to obtain aminated polysiloxane. Mix the aminated polysiloxane, p-toluenesulfonic acid and 4A molecular sieve and DMF evenly, stir and add cinnamaldehyde at 300 r / min and 55℃, and react for 6 h to obtain modified monomer.

[0029] The molar ratio of p-phenylenediamine and allyl alcohol glycidyl ether in step B1 is 1:4, and the molar ratio of intermediate di and p-nitrophenylboronic acid is 1:2.

[0030] The molar ratio of intermediate tri and trichlorosilane in step B2 is 1:4, the amount of chloroplatinic acid is 1‰ of the mass of trichlorosilane, and the molar ratio of lithium dimethylhydrosilyl alcohol, trifluoropropylmethylcyclotrisiloxane and Si-Cl on intermediate tetra is 1:5:1.

[0031] The ratio of modified polysiloxane, zinc powder, deionized water, DMF and concentrated hydrochloric acid in step B3 is 152g:15g:50mL:200mL:50mL, the mass fraction of concentrated hydrochloric acid is 36%, the molar ratio of amino group and cinnamaldehyde on the aminated polysiloxane is 1:1, and the amount of p-toluenesulfonic acid is 1%.

[0032] Example 3: A conductive coating for carbon-coated aluminum foil is prepared by the following steps: Step A1: Mix acrylic acid, diethanolamine, p-toluenesulfonic acid, hydroquinone and DMF evenly, purge with nitrogen, and react for 3 hours at 150 r / min and 85°C to obtain intermediate one. Mix intermediate one, mercaptoacetic acid, p-toluenesulfonic acid and DMF evenly, and react for 8 hours at 300 r / min and 115°C to obtain the modifier. Step A2: Mix acrylic acid, acrylamide, acrylonitrile, and DMF evenly. Stir and add azobisisobutyronitrile at 200 r / min and 80°C. After reacting for 20 min, add the modified monomer and continue reacting for 4 h. Adjust the pH to 6.5 to obtain pretreated polyacrylic acid. Mix the pretreated acrylic acid, modifier, chloroplatinic acid, and DMF evenly. React at 300 r / min and 85°C for 8 h to obtain modified polyacrylic acid. Step A3: Weigh the following raw materials in parts by weight: 10 parts conductive carbon black, 97 parts few-layer graphene, 150 parts modified polyacrylic acid, 5 parts silver powder, 30 parts polyvinylpyrrolidone, and 1500 parts solvent. Mix the raw materials evenly to obtain a carbon-coated aluminum foil conductive coating.

[0033] In the preparation of intermediate one described in step A1, the molar ratio of acrylic acid and diethanolamine is 1:1, the amount of p-toluenesulfonic acid is 1% of the mass of ethylene glycolamine, and the amount of hydroquinone is 1‰ of the mass of ethylene glycolamine. In the preparation of the modifier, the molar ratio of intermediate one and mercaptoacetic acid is 1:2, and the amount of p-toluenesulfonic acid is 1.5% of the mass of intermediate one.

[0034] The weight ratio of acrylic acid, acrylamide, acrylonitrile and the modifying monomer in step A2 is 70:30:15:4. The amount of azobisisobutyronitrile is 3‰ of the sum of the mass of acrylic acid, acrylamide and acrylonitrile. The molar ratio of Si-H bonds on the pretreated acrylic acid to the modifier is 1:1. The amount of chloroplatinic acid is 1‰ of the mass of the modifier.

[0035] The few-layer graphene mentioned in step A3 has 10 layers and a particle size of 8 μm. The silver powder has a particle size of 3 μm. The polyvinylpyrrolidone is of type K30. The solvent is a mixture of deionized water, ethanol, n-propanol, isopropanol and n-butanol in a mass ratio of 10:5:2:2:1.

[0036] The modified monomer is prepared by the following steps: Step B1: p-phenylenediamine, allyl alcohol glycidyl ether and DMF are mixed and reacted for 5 hours at a speed of 150 r / min, a temperature of 70 °C and a pH of 12 to obtain intermediate two. Intermediate two, p-nitrophenylboronic acid and DMF are mixed and reacted under nitrogen protection at a speed of 200 r / min, a temperature of 115 °C and a pH of 8 for 5 hours to obtain intermediate three. Step B2: Intermediate tri, trichlorosilane, chloroplatinic acid and DMF are mixed evenly, and nitrogen gas is introduced for protection. The mixture is reacted for 8 hours at a speed of 300 r / min and a temperature of 85°C to obtain intermediate tetra. Lithium dimethylhydrosilyl alcohol and DMF are mixed and stirred at a speed of 200 r / min and a temperature of 0°C. Trifluoropropylmethylcyclotrisiloxane is added, the temperature is raised to 30°C, and the mixture is reacted for 24 hours. Then, a modifier is added, and the reaction is continued for 1.5 hours to obtain modified polysiloxane. Step B3: Mix the modified polysiloxane, zinc powder, deionized water and DMF evenly, stir and add concentrated hydrochloric acid at 80 r / min and 95 ℃, and react for 4 h to obtain the aminated polysiloxane. Mix the aminated polysiloxane, p-toluenesulfonic acid and 4A molecular sieve and DMF evenly, stir and add cinnamaldehyde at 500 r / min and 60 ℃, and react for 7 h to obtain the modified monomer.

[0037] The molar ratio of p-phenylenediamine and allyl alcohol glycidyl ether in step B1 is 1:4, and the molar ratio of intermediate di and p-nitrophenylboronic acid is 1:2.

[0038] The molar ratio of intermediate tri and trichlorosilane in step B2 is 1:4, the amount of chloroplatinic acid is 1‰ of the mass of trichlorosilane, and the molar ratio of lithium dimethylhydrosilyl alcohol, trifluoropropylmethylcyclotrisiloxane and Si-Cl on intermediate tetra is 1:5:1.

[0039] The ratio of modified polysiloxane, zinc powder, deionized water, DMF and concentrated hydrochloric acid in step B3 is 152g:15g:50mL:200mL:50mL, the mass fraction of concentrated hydrochloric acid is 36%, the molar ratio of amino group and cinnamaldehyde on the aminated polysiloxane is 1:1, and the amount of p-toluenesulfonic acid is 1%.

[0040] Comparative Example 1: This comparative example did not include silver powder, but the remaining steps were the same as in Example 1.

[0041] Comparative Example 2: Compared with Example 1, this comparative example uses hexamethylcyclotrisiloxane instead of trifluoropropylmethylcyclotrisiloxane, and the other steps are the same.

[0042] Comparative Example 3: This comparative example uses modified polysiloxane instead of modified monomer, but the other steps are the same as in Example 1.

[0043] The conductive coatings prepared in Examples 1-3 and Comparative Examples 1-3 were tested according to GB / T6739-2006 "Determination of Hardness of Paint Film by Pencil Method for Paints and Varnishes"; the adhesion was tested on the coating test panels using a single test column from one side according to GB / T5210-2006 "Adhesion Test of Paints and Varnishes by Pull-Off Method"; the flexibility was tested according to GB / T1731-2020 "Determination of Flexibility of Paint Film and Putty Film". The smaller the value, the better the toughness of the coating. The test results are shown in Table 1 below.

[0044] Table 1 hardness 6H 6H 6H 4H 4H 3H Adhesion 4.25 4.32 4.36 4.12 3.74 2.81 flexibility 2 2 2 3 3 5 As shown in Table 1, this application has excellent mechanical properties and can meet the requirements for the use of carbon-coated aluminum foil.

[0045] The above description is merely an example and illustration of the concept of the present invention. Those skilled in the art can make various modifications or additions to the specific embodiments described or use similar methods to replace them, as long as they do not deviate from the concept of the invention or exceed the scope defined in the claims, they should all fall within the protection scope of the present invention.

Claims

1. A conductive coating for carbon-coated aluminum foil, characterized in that: It is made by the following steps: Step A1: Mix acrylic acid, diethanolamine, p-toluenesulfonic acid, hydroquinone and DMF evenly, purge with nitrogen gas for protection, and react to obtain intermediate one. Mix intermediate one, mercaptoacetic acid, p-toluenesulfonic acid and DMF and react to obtain the modifier. Step A2: Mix and stir acrylic acid, acrylamide, acrylonitrile and DMF and add azobisisobutyronitrile. After reaction, add the modifying monomer and continue the reaction to obtain pretreated polyacrylic acid. Mix and react the pretreated acrylic acid, modifier, chloroplatinic acid and DMF to obtain modified polyacrylic acid. Step A3: Weigh the following raw materials in parts by weight: 3-10 parts conductive carbon black, 90-97 parts few-layer graphene, 100-150 parts modified polyacrylic acid, 3-5 parts silver powder, 15-30 parts polyvinylpyrrolidone and 500-1500 parts solvent. Mix the raw materials evenly to obtain a carbon-coated aluminum foil conductive coating. In the preparation of intermediate one described in step A1, the molar ratio of acrylic acid and diethanolamine is 1:1, and in the preparation of the modifier, the molar ratio of intermediate one and thioglycolic acid is 1:

2. The weight ratio of acrylic acid, acrylamide, acrylonitrile and modified monomer in step A2 is 60-70:20-30:10-15:2-4, and the molar ratio of Si-H bonds on the pretreated acrylic acid to the modifier is 1:

1. The modified monomer is prepared by the following steps: Step B1: Mix p-phenylenediamine, allyl alcohol glycidyl ether and DMF to prepare intermediate two. Mix intermediate two, p-nitrophenylboronic acid and DMF, and carry out the reaction under nitrogen protection to prepare intermediate three. Step B2: Mix intermediate tri, trichlorosilane, chloroplatinic acid and DMF evenly, purge with nitrogen and react to obtain intermediate tetra. Mix lithium dimethylhydrosilyl alcohol and DMF and stir, add trifluoropropylmethylcyclotrisiloxane, heat and react, add modifier and continue reaction to obtain modified polysiloxane. Step B3: Mix and stir the modified polysiloxane, zinc powder, deionized water and DMF and add concentrated hydrochloric acid to react and obtain aminated polysiloxane. Mix and stir the aminated polysiloxane, p-toluenesulfonic acid and 4A molecular sieve and DMF and add cinnamaldehyde to react and obtain modified monomer. The molar ratio of p-phenylenediamine and allyl alcohol glycidyl ether in step B1 is 1:4, and the molar ratio of intermediate di and p-nitrophenylboronic acid is 1:

2. The molar ratio of intermediate tri and trichlorosilane in step B2 is 1:4, and the molar ratio of lithium dimethylhydrosilyl alcohol, trifluoropropylmethylcyclotrisiloxane and Si-Cl on intermediate tetra is 1:5:

1. The ratio of modified polysiloxane, zinc powder, deionized water, DMF and concentrated hydrochloric acid in step B3 is 152g:15g:50mL:200mL:50mL, and the molar ratio of amino group and cinnamaldehyde on the aminated polysiloxane is 1:

1.

2. The conductive coating for carbon-coated aluminum foil according to claim 1, characterized in that: The solvent mentioned in step A3 is a mixture of deionized water and alcohol in any proportion, wherein the alcohol is one or more of ethanol, n-propanol, isopropanol and n-butanol in any proportion.

Citation Information

Patent Citations

  • Current collector composite slurry, preparation method of current collector composite slurry, composite positive current collector and application of composite positive current collector

    CN119955364A

  • Fluoropolyether-containing polymer-modified silane, surface treating agent, and article

    US20160319071A1